Changes in Anthropometry Measurement among Human Immunodefi ciency Virus/Acquired Immune Defi ciency Syndrome (HIV/AIDS) Patients Received Antiretroviral Treatment - Adi Irawan; Doni Priambodo Wijisaksono; Rizka Humardewayanti; Yanri WIjayanti (Faculty of Medicine Universitas Gadjah Mada, 2014)
ABSTRACTBackground: Estimated nearly 38.6 million people infected by HIV and 2.8 million died in 2005. Evidence suggests the existence of a very important relationship between the output and improved nutritional statusin HIV/AIDS patients. Poor nutritional status in HIV/AIDS can be caused by several factors, namely the intake and absorption of inadequate nutrition, metabolic changes, hyper metabolism, or a combination of these, changes in the gastrointestinal tract as well as interactions between drugs and nutrients. Losing weight remains on the HAART (Highly Active Antiretroviral Therapies) era, but the problems are the side effects of HAART and lipodystrophy.Objective: The purpose of this study is to determine the provision of anti- retroviral effect on changes in anthropometric values people with HIV/AIDS. Method: The study is using the one group pre-posttest design (quasi-experimental), by assessing changes in anthropometric values in subjects with HIV before and after the administration of ARVs. Analysis of the data is computerized by a computer program Result: Obtained 30 samples of the study with anthropometric changes pre and post ARVs 6 months. Theweight was 51.4 ± 9.12 to 53.6 ± 8.68 with a p-value 0.001. Body Mass Index (BMI) was 19.98 ± 3.47 into 20.84 ± 3.35 with a p-value 0.001 and upper arm circumference 24.13 ± 3.62 into 24.95±3.48 with a p-value 0.003. The provision of antiretroviral drugs for 6 months infl uences the change in nutritional status of HIV patients are assessed by anthropometric measure. Signifi cant changes in the changes body weight, BMIand upper arm circumference. Changes in anthropometric values ARV Efavirenz group and non-Efavirenz meaningful change signifi cant in skinfold thickness obtained at the value of p 0.010.Conclusion: There were no signifi cant changes in anthropometric values compared to patients with early stage HIV and advanced stage after 6 months of antiretroviral therapy.Keywords: HIV, antiretroviral drugs, anthropometric, nutritional status